Pendampingan Peningkatan Keterampilan dan Pemasaran Hasil Kerajinan Limbah Kain Berbasis ICT pada KWT Salimah Nagari Sungai Abang Lubuk Alung - Dahri, Nuraeni; Sutardjo, Agus; Weriza, Jusmita; Hadi, Harry Setya; Rinaldo, Jhon; Adawiyah, Dina (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of providing assistance through PKM activities is to improve the skills of craftsmen in making products from fabric waste and ICT-based marketing systems in the KWT Salimah craftsmen group in Sungai Abang Lubuk Alung nagari. The PKM method used is education with a lecture-discussion approach and Learning By Doing through practical work. Counselling assistance on how to use digital devices to market and increase the sales volume of KWT Salimah merchandise which has only been done conventionally or offline. This counselling contains education about using digital devices wisely and appropriately and creating social media and e-commerce whose designation is to sell online creatively. The results obtained from this extension activity are the increase in digital knowledge and skills of KWT Salimah members regarding digital literacy, information, and media as well as a change in mindset about business in the industrial era 4.0. Increased knowledge and skills in processing fabric waste with new products that are directly practised can be achieved. The results of this PKM service can also improve and increase the knowledge and skills of KWT Salimah members in developing a fabric waste handicraft business which can have an impact on improving the household economy of residents of Sungai Abang nagari, Lubuk Alung Padang Pariaman